A Child with Intermittent Crying - Abdullah Khan (377292) (2022)
Rare earth magnets are known to be ingested by children. Neodymium or rare earth magnets are significantly more powerful than other magnets. If multiple beads of these magnets are ingested, they can cause fistulas, ulcers, and intestinal perforations.The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition suggests removing multiple magnets from the esophagus and stomach. Multiple magnets beyond the pylorus can be managed either conservatively if patient remains asymptomatic or surgically if the patient becomes symptomatic. We came across a child with unwitnessed ingestion of rare earth magnets presenting as a case of intermittent crying. The images suggested that the rare earth magnets were stuck at the gastroesophageal junction and were removed endoscopically. To our knowledge this is the first case with rare earth magnets at the gastroesophageal junction Other Information Published in: Visual Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.visj.2022.101579